PERBEDAAN KAPASITAS DAN KAPABILITAS PETANI PADI DAN BAWANG MERAH DALAM UPAYA MENINGKATKAN PRODUKTIVITAS USAHATANI - Maesti Mardiharini; Sumardjo -; Prabowo Tjitropranoto; Dwi Sadono (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
Capacity and Capability Differences on Rice and Shallot Farmers and the Impact on the Farming Productivity. During the last two decades there has been no stepping up in the production of rice and shallots farming. This is caused by low use of research innovation as well as the slow delivery of innovations to users. On the other hand, most of farmers' perceptions on extension workers are not entirely positive. The extension activities have not answered farmers need, and low impact on improving farmers' capacity and capability. The study objectives were (1) to analyze the differences on rice and shallot farmers capacity and capability, (2) to analyze the factors affected the farmers capacity and capability, and (3) to formulate a strategic approach to increase farmers capacity, capability and their farm productivity. The research was carried out through a structured survey of rice farmers in Subang and Boyolali Districts (n=270), and shallot farmers in Cirebon, Brebes, and Grobogan districts (n=249), from May to December 2018. The results of study showed that there was differences in capacity dan capability between rice farmers and shallot farmers affecting productivity among farmers and production gaps at the farm level. The use of innovation as a result of extension activities, had a high opportunity to increase in farmers' production and income. On shallots farmers the The productivity difference among farmers on shallot commodity was relatively high, because of the gap in the application of innovation in farming activities, so that the increase in capability did not directly affect on the production and income of farmers.